Phenotypic Stability of Zea mays Grain Yield and Its Attributing Traits under Drought Stress - Ali, Fawad; Ahsan, Muhammad; Ali, Qurban; Kanwal, Naila (Frontiers in Plant Science, 2017)
Phenotypic stability under stress environment facilitate the fitness of genotype and opens new horizons to explore the cryptic genetic variation. Variation in tolerance to drought stress, a major grain yield constraint to global maize production, was identified, at the phenotypic and genotypic level. Here we found a prominent hybrid H9 that showed fitness over four growing seasons for grain yield under water stress conditions. Genotypic and phenotypic correlation of yield attributing traits over four seasons demonstrated that cobs per plant, 100 seed weight, number of grains rows per cob, total dry matter, cob diameter had positive association (r2 = 0.3-0.9) to grain yield. The perturbation was found for chlorophyll content as it showed moderate to strong association (P < 0.01) over four seasons, might be due to environment or genotype dependent. Highest heritability (95%) and genetic advance (79%) for grain yield was found in H9 over four consecutive crop growing seasons. Combined analysis over four seasons showed that studied variables together explained 85 % of total variation in dependent structure (grain yield) obtained by principle component analysis. This significant finding is the best example of phenotypic stability of grain yield in H9 and made it best fitted for grain yield under drought stress scenario. Detailed genetic analysis of H9 will help us to identify significant loci and alleles that made H9 the best fitted and it could serve as a potential source to generate novel transgressive levels of tolerance for drought stress in arid/semiarid regions.